Modes of international sourcing and the competitiveness of firms: an analysis of European survey data - Marcus Neureiter; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2009)
We draw on a recent survey of European companies to differentiate between alternative modes of international outsourcing as possible determinants of market, cost and knowledge-related aspects of the competitiveness of firms. We find that internalized modes are often superior to outside options, and using existing subsidiaries tends to be more (cost) effective than undertaking new greenfield FDI.
Keywords: F23; L24; L25; 330; International sourcing; FDI; competitiveness of firms; market access; cost reduction; core and support functions; Multinationales Unternehmen; Outsourcing; Auslandsniederlassung; Direktinvestition; Internationaler Wettbewerb; Internationale Markteintrittsstrategie; EU-Staaten